2001
DOI: 10.1177/097215090100200102
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural Managerial Skill Practices: Filipino and Chinese Managers under Japanese-style Management

Abstract: For the purpose of identifying managerial skills needed for Asian managers and examining the impact of culture on the process of managerial skill practices, a series of in-depth interviews were designed with Fili pino and Chinese managers working for Japanese joint venture corporations in the Philippines and China respectively. The interview study was designed for understanding what managerial skills are practised and needed most by foreign managers and what are the influences of Japanese corporate culture on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The regional focus clearly lies on Asia Pacific and China, which is explicitly analyzed by five studies. As a reason for this focus, the growing weight of these regions in the global economy is cited (Sharma 2010; Wakabayashi, Kondo & Chen, 2001). Three studies focused on North America or the United States and two others on Germany.…”
Section: Methodology: Identification Of Relevant Studies and Descriptmentioning
confidence: 99%
“…The regional focus clearly lies on Asia Pacific and China, which is explicitly analyzed by five studies. As a reason for this focus, the growing weight of these regions in the global economy is cited (Sharma 2010; Wakabayashi, Kondo & Chen, 2001). Three studies focused on North America or the United States and two others on Germany.…”
Section: Methodology: Identification Of Relevant Studies and Descriptmentioning
confidence: 99%
“…In Chinese companies, management level plans by considering market forces and the long-term strategic objectives of the organisation (Wakabayashi, Kondo & Chen, 2001) . However, as noted by Martinsons, Davison and Huang (2017), the failures of Chinese enterprises show that the vision of the company as well as its specific objectives, and strategic plans are less distinct .…”
Section: Planning In African and Chinese Enterprisesmentioning
confidence: 99%
“…Groupism practices such as lifetime employment and keiretsu in Japan have contributed to stronger loyalty and trust within and across firms. Wakabayashi et al (2001) indicated that Japanese managers depended on high employee commitment and self‐motivation while Chinese managers had to motivate employees through other means. Gable (2002) attributed Japanese innovate “just‐in‐time” production (JIT) to Japan's land and space constraints.…”
Section: Previous Researchmentioning
confidence: 99%